Prognostic importance of solid variant papillary thyroid carcinoma: A systematic review and meta‐analysis. Issue 7 (6th March 2018) - Vuong, Huy Gia; Odate, Toru; Duong, Uyen N. P.; Mochizuki, Kunio; Nakazawa, Tadao; Katoh, Ryohei; Kondo, Tetsuo
Abstract: Background: Solid variant papillary thyroid carcinoma (SVPTC) is a rare variant of papillary thyroid cancer (PTC) and its prognostic value is still unclear. The purpose of this systematic clinical review and meta‐analysis is to investigate the prognostic value of SVPTC in comparison with classical PTC (cPTC). Methods: Four electronic databases, including PubMed, Scopus, Web of Science, and Virtual Health Library, were searched in June 2017. Extracted data were pooled into odds ratio (OR) or hazard ratio (HR) and their corresponding 95% confidence interval (CI) using the random‐effect model. Results: From 1439 articles, we finally included 11 studies with 205 SVPTCs for meta‐analysis. Overall, SVPTC manifested a significantly higher risk for vascular invasion, tumor recurrence, and cancer mortality as compared to cPTC. The genetic profile of SVPTC was also distinct from that of cPTC. Conclusion: A case of SVPTC should be regarded as an aggressive variant of PTC because of a higher risk for tumor recurrence and mortality.